Status of wildlife trade in Palawan - Yap, Jeneferlyn (2015)
Wildlife trade involves sale of wild plants and animals, whether dead or alive and in any forms which occurs both within national borders and across international territories. The demand for these wildlife resources as illegal products is usually based on their benefits. However, due to the depletion of such resources in neighboring countries, illegal poachers and traders have gone further afield nearby countries including the Philippines. Consequently, in 1990, the Philippines was identified as one of the 25 global hotspots for species threatened with extinction. In response to this growing concern, the DENR and PCSDS have exerted various effort to abate such crimes as reflected in the improvement in the number of apprehensions involving wildlife trade. A total of 58 apprehensions were recorded in the Philippines in 2011 to 2012 while 35 apprehensions were conducted in Palawan from 2010-2014. Most of the confiscated wildlife involved are marine turtles, pangolin, butterflies and birds. Nevertheless, challenges such as lack of enforcement personnel and political issues still affect the effective implementation of the law. In response, measures to improve the existing scenario are being carried out and intensified by concerned agencies with the end in view in refining and complementing existing efforts. Several points that are needed to be given emphasis include streamlining of activities relevant to the enforcement of wildlife-related law, rules and regulations, increasing enforcement visibility, enhancing capacity among field personnel and filing of case for persecution.
Keywords: Wildlife trade; Palawan Island (Philippines)